Case Report of ICF-RS Assessment Standard in Patients with Cerebral Hemorrhage - Malan ZHANG; Wei SHEN; Linghui HE; Youcheng XU; Libin RAO (康复学报)
Objective:To evaluate the function of patients with cerebral hemorrhage and guide the clinical rehabilitation practice based on the International Classification of Function, Disability and Health Rehabilitation Set (ICF-RS).Methods:One case of cerebral hemorrhage was collected, the patient's medical history, past history, auxiliary examination, routine rehabilitation evaluation and clinical diagnosis were analyzed. The patient with cerebral hemorrhage was evaluated by ICF-RS assessment standard with 30 categories, and the patient was treated with rehabilitation intervention according to the evaluation results.After two weeks' intervention, the functional changes of patients before and after treatment were compared.Results:After two weeks' intervention, the patient's physical function, activity and participation were improved than those before treatment.Conclusion:ICF-RS assessment standard can better reflect the changes of the patient's functional level, and has good reliability and validity, It can be widely used in clinical practice.